Penyalahgunaan Wewenang oleh Notaris dalam Pembuatan Akta Pengalihan Hak atas Tanah Tanpa Izin Pemilik: Analisis Putusan Mahkamah Agung Nomor 379 K/Pid/2021 - Ulung Ajubah Tri Atmojo; Sapto Hermawan; Ayub Torry Satriyo Kusumo (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Notaries hold attributive authority to draft authentic deeds, yet the Notary Law does not clearly delineate administrative violations from criminal liability, creating a normative gap. This legal issue is analyzed through Supreme Court Decision Number 379 K/Pid/2021 concerning a land-rights-transfer deed made without the owner's consent. This normative-juridical, descriptive-analytical research applies statute, conceptual and case approaches. The findings show that the abuse of authority occurred in the substance, procedure and public-office dimensions of the notarial function, producing tripartite legal consequences in civil, criminal and administrative law. Amending the Notary Law to formulate explicit intent-based parameters is proposed as a solution to close this normative gap.